The Possibilities of Measuring and Recording the Profitability of Agricultural Farms (within the Context of a Probable Introduction of Income Tax for Agricultural Farms) - Pieczonka, Jacek (Możliwości pomiaru i ewidencji dochodowości gospodarstw rolnych (w kontekście ewentualnego wprowadzenia podatku dochodowego), 2010)
Farming in Poland is subject to special tax solutions consisting, among other things, in the exclusion of most individual farmers from the natural person's income tax system. It is a considerable deviation from the principle of universality of this tax, and consequently it causes negative effects. Of course, the implementation of income tax for agricultural farms would require keeping proper accounting records for tax purposes. The implementation of an obligation to keep records of economic events on farms could become an important factor in the process of agricultural rationalization because as a result, information helpful in making optimal and effective decisions could be obtained, and financial reports could become a basis for the evaluation of farms' financial standing.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 125, s. 121-131
Keywords: accountancy; the profitability of agricultural farms; tax for agricultural farms